The earliest Jesus group in Jerusalem - Aarde, Andries van (Verbum et ecclesia, 2004)
Church formation in the history of early Christianity emanated from the kerygma about Jesus after his death. The kerygma was based on memories of Jesus which were used in the Christian cult as both explanation and apology for the encountering of God through the traditions about the crucified, buried, resurrected, and ascended Jesus. The aim of the article is to argue that the term "the Twelve" served as a self-reference of the earliest Jesus group in Jerusalem. They regarded themselves as "apostles" and "prophets" of the "new Israel", analogous to the twelve patriarchs in the Hebrew Scriptures. Reconstructing a trail from Jesus to the earliest group in Jerusalem to Paul, the article demonstrates a fundamental difference between Paul and the Jerusalem group. They understood the notion of "the Twelve" as exchangeable for "all of Israel", represented by "all the apostles". For Paul the concept "apostles" is an expansion of "the Twelve" in Jerusalem.